Valores de vitamina D e irisina e sua correlação com a composição corporal em crianças com adrenarca precoce - Furino, Vanessa de Oliveira (Universidade Federal de São Carlos, 2016)
Introduction: Premature adrenarche (PA) is characterized by the appearance of pubic hair and/or axillary, acne and body odor before age 8 in girls and before 9 in boys and these individuals are at increased risk of developing metabolic syndrome (MetS). Vitamin D and irisin seem to have an active role in the metabolism of carbohydrates and lipids, however, little is known of the role of these hormones in the PA. Objective: To analyze the vitamin D and irisin levels in children diagnosed with PA and the relationship of these substances with body composition of these children. Methodology: a quantitative exploratory cross-sectional study that evaluated 15 children diagnosed with PA and 15 controls (C) matched recruited in the public health of the city of São Carlos, Brazil. Anthropometric data were analyzed: height, weight, waist circumference (WC), triceps skinfold thickness (TSF), systolic blood pressure (SBP) and diastolic blood pressure (DBP). The participants did tests of FSH, LH, testosterone, estradiol, blood glucose, insulin, 17OHP, total cholesterol (TC), LDL, HDL, triglycerides (TG), S-DHEA, 25(OH)D and irisin. Data analysis was performed using the GraphPad Prism 5 program. The paired Wilcoxon test was used to assess the difference between means and the correlation through the Spearman test, with 5% significance level. Results: There was no significant difference between the C and PA groups in anthropometric data. The TG levels (99 ± 14.8 mg/dl in the children C versus 68 ± 9.1 mg/dl in children with PA) (p= 0.0233) and 25(OH)D (26 ± 0.9 ng/ml in the children C versus 30.2 ± 1.6 ng/ml in children with PA) (p= 0.0307) significantly were different between groups. In group C the variable that correlated significantly with irisin was 25(OH)D (r= -0.9358); in the PA group: LDL (r= 0.5620), 17OHP (r= 0.6014), TG (r= 0.6434), insulin (r= 0.5998) and relationship glucose/insulin (r= -0.7033). In group C the variable that was significantly correlated with vitamin D was irisin (r = -0.9358); there was no significant correlation of variables with 25(OH)D in the AP group. Discussion and Conclusion: This study showed higher percentage of individuals with hyperinsulinemia, insulin resistance and CA high in the PA group, important markers of MetS and future cardiovascular disease. An innovative result of this study was the strong negative correlation between irisin and 25(OH)D found in C children, suggesting an interaction of these two hormones in these individuals, which may be related to compensatory modulation of irisin in response to changing metabolism lipid found in this group. In children with PA, the highest correlation of metabolic parameters with irisin may represent a physiological modulation of this hormone by elements related to carbohydrate metabolism (as in control children C) and a specific modulation in PA, due to the same pathophysiological mechanisms that result in unfavorable metabolic profile. Since the PA can lead to an increased risk of cardiovascular disease, these children must have a suitable and long-term clinical follow-up.
Levels of vitamin D and irisin and its correlation with body composition in children with premature adrenarche
Keywords: Adrenarca precoce; Irisina; Vitamina D; Crianças; Premature adrenarche; Irisin; Vitamin D; Children; CIENCIAS DA SAUDE::ENFERMAGEM